2015
DOI: 10.1021/acsnano.5b01042
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Membrane-Enveloped Polymeric Nanoparticles as Nanovaccine for Induction of Antitumor Immunity against Melanoma

Abstract: Cancer immunotherapy is mainly focused on manipulating patient's own immune system to recognize and destroy cancer cells. Vaccine formulations based on nanotechnology have been developed to target delivery antigens to antigen presenting cells (APCs), especially dendritic cells (DCs) for efficiently induction of antigen-specific T cells response. To enhance DC targeting and antigen presenting efficiency, we developed erythrocyte membrane-enveloped poly(d,l-lactide-co-glycolide) (PLGA) nanoparticles for antigeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
258
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(265 citation statements)
references
References 68 publications
6
258
0
1
Order By: Relevance
“…28,29 It should be noted that the hydrophobic vitamin E head portion and hydrophilic oligopeptide tail are bulky and have large surface areas, which is an essential characteristic of a good surfactant. The terminal 4 amino groups of VEOEG surfactants following preparation of nanoparticles via nanoprecipitation would locate on the surface of PLGA NPs, and facilitate both shell-crosslinking and ligand decoration with biomolecules like polysaccharides, peptides, and antibodies, affording robust and multifunctional PLGA NPs for active tumor-targeting chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 It should be noted that the hydrophobic vitamin E head portion and hydrophilic oligopeptide tail are bulky and have large surface areas, which is an essential characteristic of a good surfactant. The terminal 4 amino groups of VEOEG surfactants following preparation of nanoparticles via nanoprecipitation would locate on the surface of PLGA NPs, and facilitate both shell-crosslinking and ligand decoration with biomolecules like polysaccharides, peptides, and antibodies, affording robust and multifunctional PLGA NPs for active tumor-targeting chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…C3b receptor (CR1) can identify and scavenge the circulating immune complex. Meanwhile, it can enhance the T lymphocyte function through surface molecules of CD58, CD59 and CR3 [30,31]. We can know by analyzing the indexes of immune response in erythrocyte, that the fluorescence intensities of CR3, CD58 and CD59 and the garland number of C3bR and ICR of red blood cells in peripheral blood from the LS group were all significantly higher than those of the laparotomy group, which indicated that patients with acute gastric perforation treated by laparoscopic surgery showed slighter inhibition effect on body immune function and more satisfactory postoperative recovery of immune function.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26][27] According to the parameters, including density of polymeric cores, the mean particle sizes before and after the RBCm coating, mean surface area of …”
Section: Preparation and Physicochemical Characterization Of Rbcm-ga/mentioning
confidence: 99%
“…In consideration of enormous quantity in vivo as well as simple structure and properties, red blood-cell membrane (RBCm) was the earliest and most widely explored for building synthetic biomimetic nanocarriers. [23][24][25][26][27] RBCm coating containing membrane proteins (eg, CD47, 28 C8bp, 29 and HRP 30 ) can retain their original biological properties completely, 22 disguise NPs as RBCs, 31 evade the immune response from the mononuclear phagocyte system to prolong systemic circulation without the accelerated blood clearance phenomenon, 19 and concurrently reduce reticuloendothelial system uptake. 32 This provides more opportunity to accumulate at tumor sites.…”
Section: Introductionmentioning
confidence: 99%